ANXIOUS AND BORED; STUDENT ACADEMIC BURNOUT REVIEWED FROM SOLUTION FOCUS BRIEF COUNSELING - Khairiyah Khadijah; Hayu Stevani; Maria Oktasari; M. Ramli (Research and Development Journal of Education, 2023)
During the Covid-19 pandemic, all space for movement in the community was limited, including sekolah, learning was carried out online. In the online learning process, the number of learning targets that must be achieved by students results in burnout. One way to help students overcome bornout can be seen from the perspective of the Solution Focus Brief Counseling (SFBC) approach. This research method is a descriptive quantifiable method with a sample of 30 high school students. Sampling by incidental sampling. The instrument used is the academic burnout scale. The analysis used is RASCH modeling. Based on the results of data analysis, it shows a person reability of 0.88 while for item reability, which is 0.92, this indicates a match between the item and the respondent in answering the instrument. The most approved items by students are related to feelings of anxiety, boredom, overwhelm and distress with assignments and online learning, in this case SFBC through exception question techniques, scalling questions, miracle questions, FFST, feedback and presession change questions can help students deal with these feelings